Deconstructing, Consuming, and Informing: Two Thousand Eight Hundred Million Innocent Beings - Rojas, Carmen (2002)
This analysis does not intend to explore what the causes of the destruction of the natural environment on the face of the Earth "are", but rather to gather cases of reality that question the rigor and veracity of certain statements that appear in widely distributed official reports. Herein lies one of the most exciting tasks of the academy: analyzing the information that comes our way and producing our own knowledge and criticism.